2016
DOI: 10.3390/toxins8110326
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide: The Good, the Bad and the Unknown

Abstract: Trimethylamine N-oxide (TMAO) is a small colorless amine oxide generated from choline, betaine, and carnitine by gut microbial metabolism. It accumulates in the tissue of marine animals in high concentrations and protects against the protein-destabilizing effects of urea. Plasma level of TMAO is determined by a number of factors including diet, gut microbial flora and liver flavin monooxygenase activity. In humans, a positive correlation between elevated plasma levels of TMAO and an increased risk for major ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
316
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(355 citation statements)
references
References 56 publications
2
316
0
12
Order By: Relevance
“…58 Additionally, they also showed that low adherence to the Mediterranean diet led to decreases in urinary trimethylamine oxide levels, which is associated with higher cardiovascular risk. 58,59 Several studies have shown that consumption of foods encompassing the typical Mediterranean diet improved obesity, inflammation, and lipid profile and were associated with an increases in Lactobacillus , Bifidobacterium , and Prevotella , but with decreases in Clostridium levels. 53,60 …”
Section: Environmental Factorsmentioning
confidence: 99%
“…58 Additionally, they also showed that low adherence to the Mediterranean diet led to decreases in urinary trimethylamine oxide levels, which is associated with higher cardiovascular risk. 58,59 Several studies have shown that consumption of foods encompassing the typical Mediterranean diet improved obesity, inflammation, and lipid profile and were associated with an increases in Lactobacillus , Bifidobacterium , and Prevotella , but with decreases in Clostridium levels. 53,60 …”
Section: Environmental Factorsmentioning
confidence: 99%
“…Trimethylamine-N-oxide (TMAO), a compound that is generated by a two-step process by both the host and by gut microbiota, is implicated in the development of atherosclerosis. Dietary L-carnitine, choline, and lecithin are converted to trimethylamine by the TMA-generating lyase (CutC/D) of gut microbiota, especially Firmicutes and Proteobacteria, then host flavin-containing monoamine oxidases (FMO) are responsible for the conversion to TMAO (Rath, Heidrich, Pieper, & Vital, 2017;Velasquez, Ramezani, Manal, & Raj, 2016). Plasma TMAO concentration is positively correlated to the mortality risk in patients with stable coronary artery disease, carotid intima-media thickness in obese individuals or patients with thrombosis risk (Kiouptsi & Reinhardt, 2018;Randrianarisoa et al, 2016;Senthong et al, 2016;Wang et al, 2011;Zhu et al, 2016).…”
Section: Gut Microbiota and Cardiovascular Healthmentioning
confidence: 99%
“…TMAO enhances the accumulation of cholesterol in macrophages, the deposition of foam cells in arterial walls, and the formation of atherosclerosis, all factors associated with an increased risk for cardiovascular disease and death. 203,204 Circulating choline can also be oxidized to betaine, a metabolite involved in methylation reactions and detoxification of homocysteine, in the liver and in the kidneys. In humans, elevated plasma concentrations of TMAO, choline, and betaine are associated with an increased risk for a major adverse cardiovascular event, even after adjusting for traditional risk factors.…”
Section: Importance Of the Trimethylamine/tmao Microbiome-host Axis Imentioning
confidence: 99%
“…TMA is oxidized to trimethylamine-N-oxide (TMAO) in the liver. TMAO enhances the accumulation of cholesterol in macrophages, the deposition of foam cells in arterial walls and the formation of atherosclerosis, all factors associated with an increased risk of cardiovascular disease and death 203,204 . Circulating choline can also be oxidized to betaine, a metabolite involved in methylation reactions and detoxification of homocysteine, in the liver and in the kidneys.…”
Section: Introductionmentioning
confidence: 99%